Synthesis of highpurity-SiC and-Si3 N4 from rice hulls. - Treviño, B.; Gómez de la Fuente, María Idalia del Consuelo; Colás Ortíz, Rafael (2011)
Silicon carbide and silicon nitride were syntbesized from ashes obtained by heating rice hulls at 800C for 3 hours in argon. –SiC was produced from !he ashes by reheating tbem al 1400C fOl 8 hours in argon. whereas –S3N4. was obtained by heating tbe ashes al temperatures ranging from 1250C to 1400C for perlods of 3 to 6 hours in a nitrogen rich atmospbere. The products were characterized by infrared spectrosropy. X-ray aod scanning electro. microscopy. High purity -SiC aod –S3N4. compounds witb whiskertype m.orpbology were obtained. Itwas possible to obtain –S3N4 with.out SiC by heating the ashes for 6 hours at 125OC.